Rheology study of alkali activated marine clay binder - Wee, Suan Yin (Nanyang Technological University, 2023)
The effect of water content to metakaolin (MK) and its alkali activators on its rheological and fresh properties was investigated. The samples tested were made of MK, water and activated by calcium hydroxide, sodium hydroxide and sodium silicate in different water to solids ratio. Rheological properties that studied the flow behaviour of the samples included yield stresses, viscosity by the Bingham model and its initial and final setting times. These were achieved by the vane-in-cup rheometer and the vicatronic machine. It was found that the dynamic yield stress decreases when water content increases and is the lowest when activated by sodium silicate with sodium hydroxide due to its structural buildup process. The same activators also achieved the shortest initial and final setting times as well as compressive strengths.